STRATEGI PEMBERDAYAAN PETANI DALAM MENDUKUNG DIVERSIFIKASI PANGAN LOKAL DI KABUPATEN PANDEGLANG - Asih Mulyaningsih; Andjar Astuti (JURNAL AGRIBISNIS TERPADU, 2022)
Consumption of corn, cassava, and sweet potato as local food needs to be increased continuously as one of the food strategies to support non-food self-sufficiency. The purpose of this research is to develop a strategy for empowering farmers to support the distribution of local food. Data collection was carried out for three months, from February to April 2021. This research was carried out in Pandeglang Regency, in three centers of sweet potato corn and cassava. The samples in this study were corn and cassava farmers. and sweet potato spread in three sub-districts. The number of samples is 90 farmers. Data analysis used descriptively. The results show that it is necessary to increase the empowerment of farmers by developing empowerment strategies to support local food in the form of short and long term.